Mass spectrometry-based immunopeptidomics and computational vaccinology strategies for the identification of universal Shigella immunogenic candidates. (September 2022) - Mohammad Shabani, Nor Raihan; Khairul Hisyam Ismail, Che Muhammad; Anthony, Amy Amilda; Leow, Chiuan Herng; Chuah, Candy; Abdul Majeed, Abu Bakar; Nor, Norazmi Mohd; He, Yongqun; Banga Singh, Kirnpal Kaur; Leow, Chiuan Yee
Abstract: Shigella is a Gram-negative bacteria that cause shigellosis. Treatment with antibiotics cannot be sustained to control the bacterial infection due to the risk of antibiotic resistance. Vaccine development against the highly prevalent Shigella serotypes could provide a generous benefit in reducing the occurrence of shigellosis. The present study is aimed to identify the peptides that could be the ideal candidates for the Shigella vaccine development. THP-1 human macrophage cell lines were infected with clinical strains of Shigella flexneri 2a. The bacterial peptides bound on HLA class II molecules of infected THP-1 were analyzed and identified using the immunopeptidomics approach. Following mass spectrometry identification, a total of 14 proteins were predicted by PSORTb, CELLO, and Gneg-mPLoc as outer membrane proteins (OMPs) of Shigella . Of which, 12 OMPs were found to be conserved among Shigella species and had no significance with human proteomes. Outer membrane receptor FepA and TonB-dependent receptor were among the OMPs predicted to possess the high number of immunogenic B- and T-cell epitopes. The epitopes with high antigenicity from FepA and TonB were identified as potential peptide candidates for Shigella vaccine development. The immunoreactivity of the constructed recombinant proteins were determined using the Shigella -infected human and rabbit sera, respectively. Their protective efficacy and immune responses in controlling the Shigella infection will further be investigated in experimental animal models. Highlights: Vaccine development against Shigella serotypes has a significant impact on controlling the incidence of shigellosis. Class II HLA-peptidomes of Shigella were determined using the integration of mass spectrometry and computational approaches. FepA and TonB of Shigella encompasses promising immunogens essential for the universal Shigella vaccine development.